2010
DOI: 10.2337/db09-0630
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β-Cell Sodium-Calcium Exchange Enhances Glucose-Dependent Elevations in Cytoplasmic Calcium and Insulin Secretion

Abstract: OBJECTIVEThe sodium-calcium exchanger isoform 1 (NCX1) regulates cytoplasmic calcium (Ca2+c) required for insulin secretion in β-cells. NCX1 is alternatively spliced, resulting in the expression of splice variants in different tissues such as NCX1.3 and -1.7 in β-cells. As pharmacological inhibitors of NCX1 splice variants are in development, the pharmacological profile of β-cell NCX1.3 and -1.7 and the cellular effects of NCX1 inhibition were investigated.RESEARCH DESIGN AND METHODSThe patch-clamp technique w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Notably, the activity of the forward-mode (i.e., 1Ca 2+ out/3Na + in) of the NCX in the pancreatic β-beta-cell is sensitive to long-chain acyl-coenzyme and alterations in intracellular acyl-CoA levels may cause negatively control Ca 2+ -mediated exocytosis and insulin secretion [108]. Moreover, the forward mode of the NCX1 splice variants of that is expressed in the pancreatic β-cells (NCX1.3 and NCX1.7) exhibit an unusually high sensitivity to KB-R7943 [109] that rather selectively inhibits the reversed mode of the NCX (i.e., 1Ca 2+ in/3Na + out) in most other cell types. Consequently, the pharmacological inhibition of the NCX1 with KB-R7943 results in a considerable augmentation in glucose-stimulated increases in cytosolic Ca 2+ concentrations and insulin secretion in mouse and human β-cell islets, while KB-R7943 was without effect under non-stimulated conditions.…”
Section: Plasma Membranementioning
confidence: 99%
“…Notably, the activity of the forward-mode (i.e., 1Ca 2+ out/3Na + in) of the NCX in the pancreatic β-beta-cell is sensitive to long-chain acyl-coenzyme and alterations in intracellular acyl-CoA levels may cause negatively control Ca 2+ -mediated exocytosis and insulin secretion [108]. Moreover, the forward mode of the NCX1 splice variants of that is expressed in the pancreatic β-cells (NCX1.3 and NCX1.7) exhibit an unusually high sensitivity to KB-R7943 [109] that rather selectively inhibits the reversed mode of the NCX (i.e., 1Ca 2+ in/3Na + out) in most other cell types. Consequently, the pharmacological inhibition of the NCX1 with KB-R7943 results in a considerable augmentation in glucose-stimulated increases in cytosolic Ca 2+ concentrations and insulin secretion in mouse and human β-cell islets, while KB-R7943 was without effect under non-stimulated conditions.…”
Section: Plasma Membranementioning
confidence: 99%
“…While their contribution compared with the ER is small, membrane exchangers and pumps still play an important role in Ca 2+ homeostasis in the β‐cell. Recent studies have shown that inhibition of the sodium‐calcium exchanger isoform 1 (NCX1) results in glucose‐dependent increases in cytosolic Ca 2+ concentration and insulin secretion . Similarly, heterozygous inactivation of the plasma membrane Ca 2+ ATPase (PMCA) leads to intracellular Ca 2+ accumulation, augmented insulin release and, strikingly, improved β‐cell proliferation, viability and mass …”
Section: Introductionmentioning
confidence: 99%
“…We also performed studies in murine islets isolated from male C57BL/6J mice as previously reported (27). Islets were obtained by collagenase digestion of the pancreas, purified by Ficoll density gradient, handpicked, and then cultured for 24 hours.…”
Section: Insulin Secretion Experimentsmentioning
confidence: 99%